Some Conceptual Basis for Crime Prevention in Brazil and USA: Generic Public Policies and Control Crime Programs - Beato, Claudio; Silveira, Andréa (International Journal of Criminology and Sociology, 2018)
This paper is a comparison in crime prevention between Brazil and United States, specially regarding the role of local programs vis a vis generic social policies. In Brazil, there is a tendency to design more generic strategies of crime control. In USA, there is a style of using a more specific approaches. These differences have implication on the evaluations on crime prevention made in each country